Association between caregiver burden in family and hemodialysis compliance of chronic kidney disease patients in Aceh, Indonesia - Al-Muchtari, Teuku AZ.; Syukri, Maimun; Yusni, Yusni (Narra J, 2023)
Patient compliance toward undergoing treatment determines its success rate. Unfortunately, the compliance among hemodialysis patients is concerning. Supports from family has been suggested influence the patient compliance, especially from a family member who acts as a caregiver. The aim of this study was to determine the association between the level of caregiver burden and compliance in hemodialysis patients. A cross-sectional study was conducted at Dialysis Installation at Dr. Zainoel Abidin Hospital, Banda Aceh, Indonesia. The study sample was family members who accompanied hemodialysis patients. The minimal number of patients was determined of which 67 respondents were required and therefore recruited. Caregiver burden was collected using direct interview using Caregiver Burden Assessment questionnaire. The results revealed that twenty-four respondents (35.8%) had moderate caregiver burden, while there were only nine respondents (13.4%) had very low caregiver burden. The majority of the hemodialysis patients were non-compliant (n=38, 56.7%). A Chi-squared test indicated a significant association between the status of caregiver burden and the patient compliance to hemodialysis (p=0.011). These findings stress the importance of addressing caregiver burden in ensuring the compliance of patients receiving hemodialysis.